Antibacterial and Immunomodulatory Effects of Hexamethylenetetramine (Methenamine) Silver Nitrate; Physiology and Pharmacology; Vol. 19, iss. 4 - Plotnikov E. V. Evgeny Vladimirovich (2015, 2015)
Title screen